Honduran nursing care to pressure injuries in patients with invasive mechanical ventilation: A qualitative study - Yoselin Isabel Vallejo Bustamante; Oscar Fidel Antunez Martinez (Belitung Nursing Journal)
Background: Although substantial evidence exists regarding the treatment of pressure ulcers, there is a lack of studies demonstrating a comprehensive nursing approach for managing pressure ulcers in the ICU, particularly among patients with invasive mechanical ventilation from developing countries like Honduras. This gap in research is significant as the risk and impact of pressure ulcers on health recovery cannot be disregarded.